Type 2 Diabetes Impacts the Efficacy of Syphilis Treatment and is a Risk Factor for Late Syphilis: A Retrospective Cohort Study - Yijie Tang; Mengxiao Wu; Wenwen Xu; Jiajie Yu; Dandan Yang; Jiaqin Zhang; Lingyun Shen; Qinghui Xie; Qingqiong Luo (Acta Dermato-Venereologica)
This study examined the relationship between type 2 diabetes and late syphilis. A retrospective analysis was conducted, including 96 syphilis patients with type 2 diabetes and 122 matched non-diabetic syphilis controls. The development of late-stage syphilis and responses to initial treatment were monitored over a 2-year period. Stratified logistic regression was used to assess whether diabetes increased the risk of late syphilis. Differences in initial treatment responses between the 2 groups were evaluated using χ2 tests and Kaplan–Meier curves. The cohort study confirmed that the serological cure rate within 12 months was significantly lower in diabetic syphilis patients. Type 2 diabetes significantly impacts the efficacy of syphilis treatment and is a risk factor for late syphilis.